The barrier and the intestinal microflora - the factors determining the state of human health - Jopkiewicz, Sylwia Paulina (Journal of Education, Health and Sport, 2019)
Introduction and purpose: Protective function, immune and nutrition in the human body correspond to the intestinal barrier. As a result of excessive exposure to various factors often leads to damage or abnormalities in its functioning, which negatively affects the behavior of human health. The intestinal microflora is important in the process of metabolism, as well as the intestinal barrier plays an important role in establishing immunity and protection. The purpose of this article is to present the importance and the role played by the barrier and microflora in maintaining human health.Description of knowledge:Use of alcohol, non-steroidal anti-inflammatory drugs, antibiotics, completed parasitic infections, viral and bacterial infections, chronic stress and diet deficient in fruits and vegetables cause damage to the intestinal barrier and microflora bacterial dysbiosis.Conclusions:Damaged intestinal barrier is causing loss of control on the elements that penetrate into the bloodstream. Increased permeability of the intestinal barrier contributes to increased risk of developing various diseases.